Novel sulpiride-loaded solid lipid nanoparticles with enhanced intestinal permeability - Ibrahim WM (Dove Medical Press, 2013)
Waheed M Ibrahim,1 Abdullah H AlOmrani,2 Alaa Eldeen B Yassin31Drug Sector, Saudi Food and Drug Authority, 2Department of Pharmaceutics, College of Pharmacy, King Saud University, 3Department of Pharmaceutical Sciences, College of Pharmacy, King Saud bin Abdulaziz University for Health Sciences, National Guard Health Affairs, Riyadh, Saudi ArabiaBackground: Solid lipid nanoparticles (SLN), novel drug delivery carriers, can be utilized in enhancing both intestinal permeability and dissolution of poorly absorbed drugs. The aim of this work was to enhance the intestinal permeability of sulpiride by loading into SLN.Methods: A unique ultrasonic melt-emulsification method with minimum stress conditions was used for the preparation of SLN. The mixture of the drug and the melted lipids was simply dispersed in an aqueous solution of a surfactant at a temperature that was 10°C higher than the melting points of the lipids using probe sonication, and was then simultaneously dispersed in cold water. Several formulation parameters were optimized, including the drug-to-lipid ratio, and the types of lipids and surfactants used. The produced SLN were evaluated for their particle size and shape, surface charge, entrapment efficiency, crystallinity of the drug and lipids, and the drug release profile. The rat everted sac intestine model was utilized to evaluate the change in intestinal permeability of sulpiride by loading into SLN.Results: The method adopted allowed successful preparation of SLN with a monodispersed particle size of 147.8–298.8 nm. Both scanning electron microscopic and atomic force microscopic images showed uniform spherical particles and confirmed the sizes determined by the light scattering technique. Combination of triglycerides with stearic acid resulted in a marked increase in zeta potential, entrapment efficiency, and drug loading; however, the particle size was increased. The type of surfactant used was critical for particle size, charge, drug loading, and entrapment efficiency. Generally, the in vitro release profile demonstrated by all formulations showed the common biphasic mode with a varying degree of burst release. The everted sac model showed markedly enhanced sulpiride permeability in the case of the SLN-loaded formulation. The in situ results showed a very good correlation with the in vitro release data.Conclusion: Incorporation of sulpiride into SLN results in enhanced intestinal permeability of sulpiride, that may in turn increase overall oral absorption of the drug. The superior attributes of the prepared SLN, specifically the high particle size uniformity and drug loading capacity, is considered novel, especially given the simplicity and modest nature of the sonication method used.Keywords: ultrasonic melt-emulsification, everted sacs, atomic force microscopy, Dynasan®, stearic acid